Late‐onset epilepsy with unknown etiology: A pilot study on neuropsychological profile, cerebrospinal fluid biomarkers, and quantitative EEG characteristics: Biomarkers (non‐neuroimaging) / Multi‐modal comparisons. (7th December 2020) - Farotti, Lucia; Cesarini, Elena Nardi; Babiloni, Claudio; Salvadori, Nicola; Percio, Claudio Del; Pascarelli, Maria Teresa; Noce, Giuseppe; Lizio, Roberta; Da Re, Fulvio; Isella, Valeria; Tremolizzo, Lucio; Romoli, Michele; et al.
Abstract: Background: Despite epilepsy has been associated with cognitive decline, neuropsychological, neurobiological and neurophysiological features in patients with late‐onset epilepsy of unknown etiology (LOEU) are still unknown. This cross‐sectional study aims at investigating neuropsychological profile, cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD), and resting‐state quantitative electroencephalographic (qEEG) cortical rhythms in LOEU patients with mild cognitive impairment (LOEU‐MCI) and with normal cognition (LOEU‐CN), compared to non‐epileptic MCI (NE‐MCI) and cognitively normal (CN) controls. Method: Consecutive patients in two clinical Units diagnosed with LOEU‐CN (19), LOEU‐MCI (27), and NE‐MCI (21) were enrolled, and compared to age and sex‐matched cognitively normal subjects (CN, 11). Patients underwent standardized comprehensive neuropsychological evaluation and CSF core AD biomarkers assessment (i.e., CSF Aβ42, phospho‐tau and total tau, classified through A/T/(N) system). Recordings of resting‐state eyes‐closed electroencephalographic (EEG) rhythms were collected and cortical source estimation of delta (<4 Hz) to gamma (>30 Hz) bands with exact Low Resolution Electromagnetic Tomography (eLORETA) was performed. Result: Most of LOEU patients had MCI status at seizure onset (59%). Patients with LOEU‐MCI performed significantly worse on measures of global cognition, visuo‐spatial abilities and executive functions compared to NE‐MCI patients (p<0.05). Regarding MCI subtype, multiple‐domain MCI was 3‐fold more frequent in the LOEU‐MCI than in the NE‐MCI patients (OR 3.14, 95%CI 0.93‐10.58, p=0.06). CSF Aβ42 levels were lower in the LOEU‐MCI compared with the LOEU‐CN group. Finally, parietal and occipital sources of alpha (8‐12 Hz) rhythms were less active in the LOEU‐MCI than NE‐MCI and CN groups, and the opposite was true for frontal and temporal cortical delta sources. Conclusion: MCI status was relatively frequent in LOEU patients, involved multiple cognitive domains, and might have been driven by amyloidosis according to CSF biomarkers. LOEU‐MCI status was associated with abnormalities in cortical sources of EEG rhythms related to quiet vigilance. Future longitudinal studies should cross‐validate our findings and test the predictive value of CSF and EEG variables.